(untitled) (Research, Society and Development, 2021)
The construction sector has significant importance in socioeconomic development. However, the extraction of natural resources for the production of raw materials and the generation of waste during the construction process provide major impacts to the environment. The incorporation of civil construction waste as a raw material for the production of mortars is an alternative for minimizing impacts on the environment. Therefore, this study aimed to evaluate the potentiality of the use of the predominantly cementitious fraction of two civil construction residues (CCR) as a partial substitute for cement in coating mortars, considering their physical and mechanical performance. The waste was collected in two different locations in the city of Pelotas/RS, the first coming from the demolition of an industrial building in the central region (RCD), and the second, coming from a cementitious artifacts factory (RIPM) located in the northern part of the city. For the experiment, the reference trait was made in the proportions of 1:2:8 (cement, lime and sand) and the mass substitutions of cement by residue were performed at the levels of 5, 10 and 15%. The results showed that the incorporation of both residues can be a viable alternative, because it provides mortars with performance equivalent to that of the reference mortar.